Bone marrow mononuclear cell therapy in ischaemic stroke: a systematic review. (24th August 2016) - Kumar, A.; Prasad, M.; Jali, V. P.; Pandit, A. K.; Misra, S.; Kumar, P.; Chakravarty, K.; Kathuria, P.; Gulati, A.
Abstract : Bone marrow mononuclear cell (BM‐MNC) therapy has emerged as a potential therapy for the treatment of stroke. We performed a systematic review of published studies using BM‐MNC therapy in patients with ischaemic stroke (IS). Literature was searched using MEDLINE, PubMed, EMBASE, Trip Database, Cochrane library and clinicaltrial.gov to identify studies on BM‐MNC therapy in IS till June, 2016. Data were extracted independently by two reviewers. STATA version 13 was used for carrying out meta‐analysis. We included non‐randomized open‐label, single‐arm and non‐randomized comparative studies or randomized controlled trials (RCTs) if BM‐MNCs were used to treat patients with IS in any phase after the index stroke. One randomized trial, two non‐randomized comparative trials and four single‐arm open‐label trials (total seven studies) involving 227 subjects (137 patients and 90 controls) were included in the systematic review and meta‐analysis. The pooled proportion for favourable clinical outcome (modified Rankin Scale score ≤2) in six studies involving 122 subjects was 29% (95% CI 0.16–0.43) who were exposed to BM‐MNCs and pooled proportion for favourable clinical outcome of 69 subjects (taken from two trials) who did not receive BM‐MNCs was 20% (95% CI 0.12–0.32). The pooled difference in the safety outcomes was not significant between both the groups. Our systematic review suggests that BM‐MNC therapy is safe up to 1 year post‐intervention and is feasible; however, its efficacy in the case of IS patients is debatable. Well‐designed randomized controlled trials are required to provide more information on the efficacy of BM‐MNC transplantation in patients with IS.